2022
DOI: 10.3389/fmicb.2022.1054782
|View full text |Cite
|
Sign up to set email alerts
|

Advances, applications, and limitations of portable and rapid detection technologies for routinely encountered foodborne pathogens

Abstract: Traditional foodborne pathogen detection methods are highly dependent on pre-treatment of samples and selective microbiological plating to reliably screen target microorganisms. Inherent limitations of conventional methods include longer turnaround time and high costs, use of bulky equipment, and the need for trained staff in centralized laboratory settings. Researchers have developed stable, reliable, sensitive, and selective, rapid foodborne pathogens detection assays to work around these limitations. Recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…317 Other recent review articles that include microfluidic devices have been worked out, for instance by Gao et al, who discussed advances in microfluidic devices for foodborne pathogen detection, 318 by Shang et al with focus on advances in nanomaterial-based microfluidic platforms, 319 by Ranjbaran et al on microfluidics at the interface of bacteria and fresh produce, 320 or by Quintela et al on advances and limitations of portable and rapid detection technologies for foodborne pathogens. 321 326 Wang et al discussed microfluidic sampling and biosensing systems for foodborne E. coli and Salmonella. 327 In the context of GTI diagnosis, only a few microfluidic devices have been designed for or tested directly with human samples, in particular fecal samples.…”
Section: Diagnostic Methods and Relevant Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…317 Other recent review articles that include microfluidic devices have been worked out, for instance by Gao et al, who discussed advances in microfluidic devices for foodborne pathogen detection, 318 by Shang et al with focus on advances in nanomaterial-based microfluidic platforms, 319 by Ranjbaran et al on microfluidics at the interface of bacteria and fresh produce, 320 or by Quintela et al on advances and limitations of portable and rapid detection technologies for foodborne pathogens. 321 326 Wang et al discussed microfluidic sampling and biosensing systems for foodborne E. coli and Salmonella. 327 In the context of GTI diagnosis, only a few microfluidic devices have been designed for or tested directly with human samples, in particular fecal samples.…”
Section: Diagnostic Methods and Relevant Reviewsmentioning
confidence: 99%
“…317 Other recent review articles that include microfluidic devices have been worked out, for instance by Gao et al , who discussed advances in microfluidic devices for foodborne pathogen detection, 318 by Shang et al with focus on advances in nanomaterial-based microfluidic platforms, 319 by Ranjbaran et al on microfluidics at the interface of bacteria and fresh produce, 320 or by Quintela et al on advances and limitations of portable and rapid detection technologies for foodborne pathogens. 321 Mi et al summarized microfluidic biosensor tools for foodborne pathogenic bacteria and Su et al investigated microfluidic nucleic acid tests of foodborne viruses. 322,323 Other reviews focused on specific pathogens, such as POC methods for detection of norovirus by Zaczek-Moczydlowska et al or POC diagnosis for E. coli O157:H7 in food and water by Rani et al 324,325 Shen et al explored biosensor technologies for rapid detection of Salmonella in food.…”
Section: Gastrointestinal Tract Infectionsmentioning
confidence: 99%
“…Serological methods (i.e., immunoassays) (e.g., enzyme-linked immunosorbent assay; ELISA) [124][125][126][127][128], biosensors for the on-site detection of foodborne pathogens [129,130], DNA hybridization techniques (e.g., loop-mediated isothermal amplification; LAMP) [126,131,132], DNA fingerprinting techniques (e.g., multilocus sequence typing; MLST) [133][134][135] and above all PCR-based method and techniques (e.g., multiplex PCR; mPCR, quantitative or real time PCR; qPCR/rt-PCR), have been developed for the fastest and most efficient identification and differentiation of Campylobacter species among other foodborne pathogens. It should be noted though that some DNA fingerprinting techniques are more sophisticated (e.g., pulsed-field gel electrophoresis; PFGE, whole-genome sequencing; WGS) and require well-trained personnel with a know-how-to conduct the technique and interpret the data.…”
Section: Molecular Methods For Differentiating Campylobacter Speciesmentioning
confidence: 99%
“…Tests using Escherichia coli O157:H7 as a representative organism showed that the smartphone-based procedure could detect concentrations between 10 4 and 10 5 CFU/mL in both spinach and ground beef samples [ 153 ]. Many examples of the applications of these newer detection techniques have been mentioned extensively in various articles [ 151 , 154 , 155 , 156 ].…”
Section: Application Of Bioaffinity Nanoprobes In Food Biosensingmentioning
confidence: 99%